Can you guys help me with this problem with a little explanation on how you came to solve it and I will share the answer that was provided in the book. Thanks in Advance
Follow Math Help Forum on Facebook and Google+
note ... $\displaystyle -2^2 = -1 \cdot 2^2 = -1 \cdot 4 = -4$, and ... $\displaystyle (-2)^2 = (-1 \cdot 2)^2 = (-1)^2 \cdot 2^2 = 1 \cdot 4 = 4$ therefore ... $\displaystyle -2^2 - (-2)^2 = -4 - 4 = -8$
You got the same answer as the book. I see where I went wrong thank you for answering my question. I thought -2^2 was the same as (-2)^2 How I did it the first time: -2^2-(-2)^2= =-2^2-4 =4-4 = 0
Last edited by medlinemd; Apr 12th 2012 at 08:01 PM.
View Tag Cloud